Geochemical parameters determined in sediment cores from Lake Burgäschi, Switzerland - Luyao Tu; Paul D Zander; Sönke Szidat; Ronald Lloren; Martin Grosjean (PANGAEA, 2019)
Sediment phosphorus (P) released to surface water (a.k.a. internal P loading) is the key factor delaying lake recovery from eutrophication in many lakes. The sediment P availability and release risk into lake water can be largely evaluated by P fractions in sediments. In deep eutrophic lakes, hypolimnetic anoxia is suggested to prompt sediment-P mobility and potentially increase internal P loading on short term. However, the long-term effects hypolimnetic redox conditions and trophic state on sedimentary P-fraction retention in deep lakes are not clear. In this study we investigated two sediment cores retrieved from the deepest part of Lake Burgäschi, Switzerland. The age-depth profile based on 210Pb and 137Cs chronology dates back to the early 1900s. Sedimentary green-pigments (chlorophylls and diagenetic products) inferred from hyperspectral imaging (HSI) scanning and X-ray fluorescence (XRF)-inferred Fe/Mn ratios primarily reflect lake trophic state evolution (aquatic primary productivity) and hypolimnetic oxygenation, respectively. A sequential P-extraction with five P fractions was performed to uncover P fractionation in sediment profiles. In addition, we measured the sediment bulk elements of carbon, nitrogen and sulfur. The temporal records of P fractions concentrations and net burial rates (NBR) in sediments were investigated.